AN OVERVIEW OF THE RIVER ECOLOGICAL DIVERSITY, STRUCTURAL-FUNCTIONAL CHANGES, AND POLLUTION ASSESSMENT (International Association of Biologicals and Computational Digest, 2023)
The most significant sources of freshwater are rivers, and many different uses are made of their water. Cities near rivers have recently had a significant detrimental impact on the water quality, causing the rivers to get worse every day. This is due to the increased urbanization of these areas. The relationship between biodiversity and ecological functions is currently a major scientific topic that requires understanding and prediction.  Studies conducted on terrestrial ecosystems, for instance, have shown how species-specific traits and functional biodiversity affect key ecosystem structures and functions related to the storage and cycling of organic material. Many changes occur in ecosystem biomass because of polluting contaminants. Others are in the hydrophone structure type, while some are in the biomass summary. Greater biomass densities and a lack of diversity distinguish the contaminated river flow from the surrounding environment. Many different strategies and underlying concepts have been employed in environmental protection initiatives. Assessing the potential of any or all ecosystem components is necessary for identifying hazards. Hazard assessment describes the degree of harm any potentially harmful chemical or action will cause to ecosystem components. The assessment method needs to be extremely specific due to the changing nature of the riverine environment.
Keywords: River, ecosystem variety, Structural-functional variations, pollution evaluation